Análise da experiência do usuário (UX) no uso do sistema de rotulagem dos repositórios institucionais - Gabriela da Silva Santos Pinheiro (2022)
This is an exploratory and descriptive study which addresses the topic of Information Architecture, with a more specific focus on the labeling system, whose main objective is to investigate the User Experience (UX) in the use of descriptive metadata that make up the labeling system for institutional repositories in Higher Education Institutions in the State of Minas Gerais, Brazil. The terminological variation found in the metadata labels of the institutional repositories raised questions about the use of natural language and the standardization of the labels. In this sense, research methods in the area of UX were sought to investigate whether the metadata represented by their labels convey the concepts satisfactorily and with interaction proportional to the groups of users for which they were developed. Next, the research was carried out in three stages: 1 - Bibliographical research addressing the main themes: Information Architecture, institutional repositories and UX, composing the thematic tripod of the study; 2 - Survey of metadata labels in the interface of ten institutional research object repositories, associated with the elements of the Dublin Core metadata standard; 3 – Empirical investigation of user experience analysis, in the repositories labeling system, with the combination of two techniques: Online quiz (phase 1) and User-centered study (phase 2), with the objective of measuring data and analyzing information of participants with a representative profile of users of the repositories. With the results of step 2, it was possible to present the terminological variation of the labels, as well as to show that the metadata elements also presented variations between the repositories. Therefore, the terminological and structural inconsistencies detected in step 2 demonstrated that the selection of metadata in institutional repositories is usually guided by internal decisions, whose policies guide only the metadata standard adopted, without due attention to the guidelines that support the choice of metadata, and even less that put users at the center of this process. Then, in the UX Analysis step, phase 1 with the online questionnaire, the results projected the levels of relevance of the metadata, and it was found that most of them are disproportionate to the interests of the users, since most of the metadata did not present the expected relevance. It also allowed pointing out the set of metadata that justify the permanence in the interface of the repositories according to the perspective of the people who base their existence. In phase 2, with the user-centered study, it was possible to measure the labels that represented the consensus among the participants, going against one of the research problems, originated by the terminological variation of the labels, making it useful for eventual rectifications in the interface of the repositories. In addition, participants contributed with the recommendation of new labels to encompass alternative semantic relationships to existing labels, providing another possibility of organizing information with a focus on the user.